Revaluing the reading process of adult ESL/EFL learners through critical dialogues - Kim, Koomi; Chin, Cheongsook; Goodman, Yetta (Colombian Applied Linguistics Journal, 2004)
The authors explore language developmental processes of university English language learners. The used Retrospective Miscue Analysis (RMA) and In-depth Reading Interviews as heuristic tools to generate critical dialogues with students to reflect on their L1 and English language learning processes and perceptions. The studies show that RMA and In-Depth Reading Interviews lead the teachers researches-and english language learners to critical learnable and teachable moments.